Chapter The impact of economic insecurity on life satisfaction among German citizens - Panarello, Demetrio (Proceedings e report, 2023)
The concept of life satisfaction dates back to the Age of Enlightenment and became popular in the Nineteenth century as a synonym for 'good life'. Efforts are still underway to overcome the traditional economic criteria of well-being by broadening the definition and measurement of life satisfaction based on a large set of indicators. Although 'money cannot buy happiness', the economic dimension remains a crucial element of life satisfaction. Economic insecurity arises from unpredictable economic losses, which may affect individuals' well-being due to the feeling of failure and inability to recover. In this paper, economic insecurity is investigated for its impact on the trajectories of life satisfaction over a timespan of 30 years among working-age German citizens, grouped by age (16-29, 30-39, 40-49, 50-64) and activity sector (secondary vs. tertiary). Latent Growth Curve Models were estimated on longitudinal data from the German Socio-Economic Panel (SOEP), using individual and time fixed effects. The analyses allow us to break down the impact of economic insecurity on life satisfaction into a fixed component and a specific random component for each individual. Every year, panel respondents have been asked to provide their subjective perception of life satisfaction on a 10-point Likert scale. Economic insecurity is measured through the Bossert and D'Ambrosio's index. Our results show that economic insecurity has a negative impact on life satisfaction, which becomes more relevant for people in the 40-49 age group. This impact appears to be stronger for workers belonging to the secondary sector. Moreover, among the youngest individuals (16-29), such an impact shows a higher variability over time: therefore, within this age group, economic insecurity appears to affect life satisfaction more unpredictably. As relevant differences exist between the considered groups, our results give way to the implementation of targeted policy measures.